2011
DOI: 10.1136/bmjqs.2011.051243
|View full text |Cite
|
Sign up to set email alerts
|

Rebound in ventilator-associated pneumonia rates during a prevention checklist washout period

Abstract: OBJECTIVE To describe the washout effect after stopping a prevention checklist for ventilator-associated pneumonia (VAP). METHODS VAP rates were prospectively monitored for special cause variation over 42 months in a paediatric intensive care unit. A VAP prevention bundle was implemented, consisting of head of bed elevation, oral care, suctioning device management, ventilator tubing care, and standard infection control precautions. Key practices of the bundle were implemented with a checklist and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Our findings are in contrast with recent reports of a washout phenomenon. Cheema et al 16 described a ''checklist washout phase'' in which a rebound in the VAP incidence was observed after a significant initial decrease. Staff feedback in that study suggested that an excessive documentation burden associated with the checklist may have contributed to a ''checklist burnout'' and resulted in the impact loss observed.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings are in contrast with recent reports of a washout phenomenon. Cheema et al 16 described a ''checklist washout phase'' in which a rebound in the VAP incidence was observed after a significant initial decrease. Staff feedback in that study suggested that an excessive documentation burden associated with the checklist may have contributed to a ''checklist burnout'' and resulted in the impact loss observed.…”
Section: Discussionmentioning
confidence: 98%
“…[6][7][8][9][10] As expected, cessation of sustained efforts to monitor compliance are associated with increased rates of VAP. 11 Further, institutions are encouraged to customize the ventilator bundle to their institutional culture in order to maximize effectiveness. 12 To date, most publications describing compliance with the ventilator bundle have involved assessment of the impact on VAP rates.…”
Section: Resultsmentioning
confidence: 99%
“…Many outcomes in the field, not just CVC-BSI, involve fundamentally subjective elements—ventilator-associated pneumonia,30 preventable adverse events, ‘unexpected’ cardiac arrests in the setting of evaluations of rapid response teams, ‘unintended medication discrepancies’ and diagnostic errors, to name but a few. Social and psychological factors at the individual and institutional levels make accurate ascertainment of such outcomes, at the very least, a complex challenge, if not an unachievable goal.…”
Section: The Way Forward For Checklistsmentioning
confidence: 99%